RSS Based Tracking System for Security of Child - T.Tejarani, Mr. Y.Bhaskar Rao (International Journal of Advanced Science and Technology, 2020)
In today’s world kid and women unit of measuring low safety and have many issues regarding their safety. They need to endure among varied powerful things and must be compelled to themselves once exert altogether crucial conditions. So, for his or her security and safety puppy government has provided security through rules and regulation to society. Though their unit of measuring Se›’era existing systems for security purpose would like of advanced sensible security system is raised. Therefore, on beat such issues sensible security system for kid and women is enforced. This paper describes concerning safe academic degree secured electronic system for kid that has of Associate in Nursing Arduino controller and rate detector, sound detector. A buzzer, LCD, RSS network unit of measuring used throughout this project. Once the kid is in threat, and then the soul hand bites the bit detector that is mounted at intervals the harmful touching places of a lady kid [6]